Preclinical Evaluation of Andrographis Paniculata (burm.f.) Wall. Ex Ness as Herbal Medicine for Treatment of Breast and Prostate Cancers - Yong, Audrey Chee Hu (2011)
Most Malaysians use some forms of herbal remedy to manage their diseases and ailments. Unfortunately, most of the time, the science behind the perceived benefits of this alternative therapy has not grown in proportion to its popular usage. The Malaysian National Pharmaceutical Control Bureau (NPCB) requires all herbal medicines to meet acceptable standards for quality, safety and efficacy for the purpose of product registration. Quality control in the phytopharmaceutical products is a multistep process that covers all stages from ‘seed to pill’. It must be correctly authenticated, assessed for relative free from ontamination and assayed for active principles. In this study, Andrographis paniculata (Burm. F.) Nees (AP) or locally known as Hempedu bumi was evaluated preclinically for its quality, safety and efficacy towards development into a herbal medicine for the treatment of cancer. It is also a promising herb for the treatment of various diseases. There are three main diterpenoid lactones (DL) found in the aerial parts of AP, namely andrographolide (AGP, cytotoxic), 14-deoxy-11, 12-didehydroandrographolide (DDAG, noncytotoxic)and neoandrographolide (NAG, non-cytotoxic). These three DL were used as marker compounds in assessing the quality of the plant materials and forsubsequent in vitro and in vivo pharmacological studies. The stability and quality of dried AP material and extracts were evaluated in various storage temperatures (4 ± 2C, 25 ± 2C and 35 ± 2C) based on of the content of the marker compounds by high performance liquid chromatography (HPLC). In a preliminary study to select the best extraction solvent (ethanol, ethanol: water (1:1), dichloromethane and water), these dried extracts were tested for their cytotoxicity against cancer cell lines using the MTT cell proliferation assay. Dichloromethane extract was found to be most active. Dichloromethane extract was then standardised to contain 15-20% w/w of AGP, 1-5%w/w of DDAG and 1-3% w/w of NAG of the extract weight. This extract was used throughout the in vitro and in vivo studies. It was found that the extract had improved cytotoxicity when the amount of AGP is equivalent to the pure AGP. This prompted an investigation of whether the DLs have combination cytotoxic effect in cancer cell lines. AGP-NAG and AGP-DDAG combinations produced profound synergistic cytotoxic effect in MCF-7 (breast) and DU 145 (prostate) cancer cells. The acute toxicity of this extract was determined in mice and rats, with escalating dosages from 100 mg/kg to 2 g/kg by oral administration, and no reduction of weight in the animals was observed. The plasma DL levels were determined in mice and rats administered with AP extract at the doses of 250 mg/kg. The 250 mg/kg and 500 mg/kg doses were applied in the therapeutic studies using nude mice xenografted with breast and prostate tumours. The results from the stability study showed that the suitable storage temperature for dry AP material was at 35ºC up to 12 months to maintain content of AGP ≥ 70% of the initial content, and for the crude ethanol extract was at 35ºC for up to 6 months. For pharmacokinetic study in rodents (BALB/c, NU/Nu mice and rats), when 250 mg/kg dose of AP extract was administered orally, the maximum plasma concentrations (Cmax) of DLs were found to be in the following ranges: AGP (2.1 – 5.3 μM), NAG (2.3 – 6 μM) and DDAG (3.1 – 4.7 μM). Preclinical therapeutic study revealed antitumor activity of AP extract against DU 145 prostate but not against MDA-MB-231 breast tumour xenografts. It is highly suggestive that the synergistic cytotoxic effect of DLs may have contributed to the in vivo antitumour activity of AP extract. This study also established suitable storage conditions for AP dry materials to preserve the quality in order to obtain reliable and consistent amounts of the DLs in extracts for in vitro and in vivo studies.